2018
DOI: 10.1021/acs.langmuir.7b03896
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Laws in Directional Spreading of Droplets on Wettability-Confined Diverging Tracks

Abstract: Spontaneous pumpless transport of droplets on wettability-confined tracks is important for various applications, such as rapid transport and mixing of fluid droplets, enhanced dropwise condensation, biomedical devices, and so forth. Recent studies have shown that on an open surface, a superhydrophilic track of diverging width, laid on a superhydrophobic background, facilitates the transport of water from the narrower end to the wider end at unprecedented rates (up to 40 cm/s) without external actuation. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 70 publications
4
69
0
Order By: Relevance
“…A facile and scalable approach to produce superhydrophobic and superhydrophilic spatial domains on square aluminum samples of dimensions 100 mm × 100 mm (mirror-finish 6061 aluminum sheets, 2 mm thick, McMaster-Carr) was employed; the method (Fig. 1) is the one employed by Koukoravas et al [61] and Sen et al [62]. The metal plate samples were initially treated with a 5 M HCl solution (ACS reagent 37%, Sigma-Aldrich) for 4 min (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A facile and scalable approach to produce superhydrophobic and superhydrophilic spatial domains on square aluminum samples of dimensions 100 mm × 100 mm (mirror-finish 6061 aluminum sheets, 2 mm thick, McMaster-Carr) was employed; the method (Fig. 1) is the one employed by Koukoravas et al [61] and Sen et al [62]. The metal plate samples were initially treated with a 5 M HCl solution (ACS reagent 37%, Sigma-Aldrich) for 4 min (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…location, t is time, γ and μ denote the fluid surface tension and viscosity, respectively. 37,60 It was found that the spreading front of the water progresses along the track as the square root of time,…”
Section: Dynamics Of Fluid Transport Within the All-graphene Open Micmentioning
confidence: 99%
“…This agrees with a previous report of pumpless water spreading on hydrophilic tracks. 60 A fitting with D values of 5.5 and 7.3 for 2 mm and 1.5 mm initial channel width; respectively, are plotted in dashed lines (Figure 4b). The fitting of 1.5-mm and 2-mm channel width (Figure 4b) displayed good agreement with the experimental results while fitting with results garnered from a 1-mm channel did not ( Figure S1).…”
Section: Dynamics Of Fluid Transport Within the All-graphene Open Micmentioning
confidence: 99%
“…Since the moving path of the laser can be designed and controlled by computer, the serial-wedge-shaped wettability pattern with adjustable size composed of the exterior surrounding superhydrophilic region with water contact angle of 0° and inside interior superhydrophobic region with water contact angle of 159.0±2.3° was obtained. The laser etching processes were inspired by Hwang et al 34 and Megaridis et al 35,36…”
Section: Fabrication Of the Serial-wedge-shaped Wettability Patternmentioning
confidence: 99%